Governing the invasive trophoblast: current aspects on intra- and extracellular regulation - Fitzgerald, Justine Sayuri; Germeyer, Ariane; Huppertz, Berthold; Jeschke, Udo; Knöfler, Martin; Moser, Gerit; Scholz, Christoph; Sonderegger, Stefan; Toth, Bettina; Markert, Udo R. (American journal of reproductive immunology, 2010)
Citation Fitzgerald JS, Germeyer A, Huppertz B, Jeschke U, Knöfler M, Moser G, Scholz C, Sonderegger S, Toth B, Markert UR. Governing the invasive trophoblast: current aspects on intra- and extracellular regulation. Am J Reprod Immunol 2010 This review summarizes several aspects especially of regulating factors governing trophoblast invasion. Those include the composition of the extracellular matrix containing a variety of matrix metalloproeinases and their inhibitors, but also intracellular signals. Furthermore, a newly described trophoblast subtype, the endoglandular trophoblast, is presented. Its presence may provide a possible mechanism for opening and connecting uterine glands into the intervillous space. Amongst others, two intracellular signalling pathways are crucial for regulation of trophoblast functions and development: Wnt- and signal transducer and activator of transcription (STAT)3 signalling. Wnt signalling promotes implantation, placentation and trophoblast differentiation. Several Wnt-dependent cascades and regulatory mechanisms display different functions in trophoblast cells. The STAT3 signalling system is fundamental for induction and regulation of invasiveness in physiological trophoblastic cells, but also in tumours. The role of galectins (Gal) in trophoblast regulation and placenta development comes increasingly into focus. The Gal- 1-4, 7-10 and 12-14 have been detected in humans. Detailed information is only available for Gal-1, -2, -3, -4, -9 and -12 in endometrium and decidua. Gal-1, -3 and -13 (-14) have been detected and studied in trophoblast cells.
Gesehen am 09.05.2023